Analysis Of Divorce During The Pandemic In Central Lombok - wardah nuroniyah (Cita Konsultindo Research Center, 2023)
During the COVID-19 pandemic, divorce in Praya, Central Lombok, increased. Based on this, this study aims to identify how high divorce cases occur during the pandemic in Praya, Central Lombok. Researchers use a qualitative approach. This research is field research; researchers go directly into the field to conduct interviews and collect documents, which research is carried out at the Praya Religious Court. The result of this study is the Praya Religious Court annual report for 2021. The biggest reasons for divorce are economical 59%, disputes 23%, domestic violence 10%, and 5% for infidelity cases. The Praya Religious Court's 2022 annual report shows that the biggest reasons for divorce are 60% and 40% economic disputes, 20% domestic violence, and 10% infidelity cases. In households, daily disputes occur that are caused by several factors. According to Mrs A, the Case Manager, it was explained that the increase in divorces from 2021 to 2022 touched 100,393 people, an increase of 50% compared to 2021 with 78,724 people.